Acute Facial Nerve Palsy in Children: Gold Standard Management - Delphine Wohrer; Thomas Moulding; Luigi Titomanlio; Léa Lenglart (MDPI AG, 2022)
Facial nerve palsy (FNP) is a common illness in the paediatric emergency department. Missed or delayed diagnosis can have a serious impact on a patient's quality of life. The aim of this article is to give a recent overview of this pathology in terms of the causes, diagnosis, red flag symptoms, complementary examinations, treatments and follow-up in the child population. In cases of acquired, acute onset and isolated FNP, Bell's palsy can be assumed, and no further investigation is required. In any other scenario, complementary examinations are required. Treatment depends on the aetiology. Corticosteroids, in addition to antiviral medication, are recommended to treat Bell's palsy whenever a viral infection is suspected. However, the lack of randomised control trials in the paediatric population does not allow us to comment on the effectiveness of these treatments. In all cases, treated or not, children have a very good recovery rate. This review emphasises the necessity of randomised control trials concerning this frequent neurological pathology in order to better treat these children.